Evolutionary Community Ecology: Time to Think Outside the (Taxonomic) Box. (April 2018) - Wilcox, Taylor M.; Schwartz, Michael K.; Lowe, Winsor H.
Abstract : Ecologists and evolutionary biologists have long been interested in the role of interspecific competition in the diversification of clades. These studies often focus on a single taxonomic group, making the implicit assumption that important competitive interactions occur only between closely related taxa, despite abundant documentation of intense competition between species that are distantly related. Specifically, this assumption ignores convergence of distantly related competitors on limiting niche axes and thus may miss cryptic effects of distantly related competitors on the evolution of focal clades. For example, distantly related competitors may act as important drivers of niche conservatism within clades, a pattern commonly ascribed to evolutionary constraints or the abiotic environment. Here we propose an alternative model of how niche similarity evolves when the functional traits of interest are mediated by unrelated phenotypic traits, as is often the case for distantly related competitors. This model represents an important conceptual step towards a more accurate, taxonomically inclusive understanding of the role that competition plays in the micro- and macroevolution of interacting species. Highlights: Studies of evolutionary community ecology often assume that competitive interactions occur primarily and most intensely between closely related species, implicitly invoking the competition-relatedness hypothesis. This competition-relatedness assumption is at odds with recent theory and a wealth of empirical studies demonstrating intense competition between distantly related species. Here we provide an alternative, taxonomically inclusive framework for understanding the relationship between evolutionary relatedness and competitive interactions. This framework indicates an approach to evolutionary community ecology that relies on field and experimental data to detect species interactions and resource overlap rather than inference from phylogenetic or morphological similarity alone. A more accurate picture of the role that species interactions play in the assembly and evolution of communities will require that researchers think critically about their systems and be prepared to work outside traditional taxonomic constraints.